EFFICIENCY OF LAND TRANSFORMATION IN THE LAND OF SOLAR ENERGY (KREMENCHUK TOWN AS AN EXAMPLE): Array - Klyuka, O.; Shelkovska, I.; Mikhno, P.; Nesterenko, S. (Municipal economy of cities. Series: «Economy science», 2021)
The article considers the problems of modern use of urban areas, which are mostly related with the lack of reasonable scientifically and economically rational land policy. The issues of rational urban land using and land management in settlements have been studied by many domestic scientists, but to achieve the goal of rational and efficient land using, there is a need to continue research on these issues, especially at the regional and local levels. In particular, this applies to the formation of the mechanism of payment for land in conditions where the collection of taxes on labor and entrepreneurship significantly exceeds the amount of payment for land and other natural resources. The article gives an example of effective transformation of reserve lands which are not provided for permanent use and rent, located in the peripheral zone of the city, in the land of solar energy. The issue is considered from the standpoint of the value of unused urban land in their ability to generate additional income. Calculations to determine the efficiency of land transformation in the land of solar energy were made on the example of the commissioned solar power plant LLC «NOVE TEPLO", which is in the northern industrial hub of Kremenchuk, Poltava region, which covers an area of ​​150.00 hectares, and the total capacity of installed solar panels 75 MW. The total income of land transformation from reserve lands to solar energy lands for 10 years and rent income from 150 hectares of land for the specified period for reserve lands in Kremenchuk according to the values ​​of capitalized rent income standards are determined. The total income after the transformation of land was almost 300 times higher than the total income received before the transformation. Rating of ground-based SES was created by using the PV GIS web application. This tool allows you to estimate the average monthly and annual energy production from a solar electrical system connected to the grid. PV GIS calculates the optimal slope and slope exposure, which maximizes annual energy production.